DEVELOPMENT OF PARTICULATE MUCOADHESIVE GEL FOR INTRANASAL DELIVERY - Gaikwad, Dinanath; Kurane, Padmini; Mali, Dipak; Jadhav, Namdeo (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this research work was to develop mucoadhesive particulates gel of Propranolol HCl for intranasal delivery. Method: Drug loaded mucoadhesive particulates were prepared by spray drying technique using polymers such as HPMC K100 and Carbopol 934P. Batches were prepared according to 32 factorial designs. Result: The mucoadhesive particulates prepared were evaluated for different parameters like drug content, entrapment efficiency, mucoadhesive strength and in vitro drug release. IR, XRD and DSC study revealed that there were no interaction occurs between drug and excipients and confirming reduction in crystallinity. The swelling index and encapsulation efficiency was found to be (0.9266%), (97.44%), angle of repose, Carr's compressibility index falls in acceptable limits. At the end of 10 hr optimized batch showed 90.23 % drug release and followed zero order release kinetics. Conclusion: Conclusion from result of the studies such as increase in the concentration of polymers contributed in drug release retardation. Although, prepared formulation of nasal administration can be a value addition in treatment for heart diseases like angina pectoris, myocardial